Atonement and comparative theology : the cross in dialogue with other religions - Cornille, Catherine (Comparative theology--thinking across traditions., 2021)
"The central Christian belief in salvation through the suffering, death, and resurrection of Jesus Christ remains one of the most intractable mysteries of Christian faith. Throughout history, it has given rise to various theories of atonement, many of which have been subject to critique as they no longer speak to contemporary notions of evil and sin or to current conceptions of justice. One of the important challenges for contemporary Christian theology thus involves exploring new ways of understanding the salvific meaning of the cross. In Atonement and Comparative Theology, Christian theologians with expertise in Judaism, Islam, Hinduism, Buddhism, Daoism, and African Religions reflect on how engagement with these traditions sheds new light on the Christian understanding of atonement by pointing to analogous structures of sin and salvation, drawing attention to the scandal of the cross as seen by the religious other, and re-interpreting aspects of the Christian understanding of atonement. Together, they illustrate the possibilities for comparative theology to deepen and enrich Christian theological reflection"--